Pengaruh Kompetensi, Disiplin Kerja dan Beban Kerja terhadap Kinerja Penyidik Dit Reskrimum Polda Bengkulu - Dinda Yulistin; Tito Irwanto; Iswidana Utama Putra (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2022)
The purpose of this study was to determine the effect of competence, work discipline and workload on the performance of Investigators of the Criminal Investigation Directorate of the Bengkulu Police. The sample in this study was 80 investigators from the Directorate of Criminal Investigation at the Bengkulu Police. The sampling technique was a census and the data were collected using a questionnaire and the analytical methods through validity test, through validity test, reliability test, classical assumption test, multiple linear regression, determination test and hypothesis testing. The results of this study indicate that competence has a positive and significant effect on the performance of investigators from the Directorate of Criminal Investigation at the Bengkulu Police, because the significant value of 0.000 is smaller than 0.05. This means that the increasing competence affected the performance. Work Discipline has a positive and significant effect on the performance of Bengkulu Police Criminal Investigation Department investigators, because the significant value of 0.027 is smaller than 0.05, the more attention to work discipline of members will increase. This illustrates that with good work discipline between investigators and leaders and between investigators and other investigators, performance can be improved. Workload has a positive and significant influence on the performance of Bengkulu Police Criminal Investigation Directorate because the significant value of 0.000 is less than 0, 05. This illustrates that the existence of a workload that is in accordance with the skills and knowledge can improve the performance of investigators. The results of the f test indicate a significant influence between competence, work discipline and workload on performance together. The coefficient of determination of R square is 0.814. This means that competence, work discipline and workload affect performance by 81.4% while the rest (100-81.4% = 18.6%) is influenced by other causal factors not examined in this study.